FAMILIARIZATION OF FOOTBALL PLAYERS’ TRAINING SESSIONS - Muminov Sherzod Ilyosovich; Quvvatov Umid Tursunovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Basic and additional classes are planned and conducted in the training process. The main tasks of a certain stage of preparation are solved in the main classes. In additional classes, special training tasks are solved, in particular, the restoration of athletic performance. Based on the localization of the orientation of the means and methods used in the classroom, there are classes and complex orientation.